Resistance of sorghum hybrids to sorghum aphid - Avellar,G. S. (2022)
Abstract The aphid Melanaphis sorghi (Theobald) (Hemiptera: Aphididae), which infest the sorghum crop, has been an economically important pest which have been causing severe damage to sorghum crops in Brazil since 2019. These species have been observed mainly at the end of vegetative stage and beginning of reproductive stage of plants. Their high reproductive rate on sorghum raises concerns about these pests. Therefore, the present study aimed to estimate the life expectancy and fertility tables of Melanaphis sorghi fed on 15 hybrids of grain sorghum, in order to know the resistance characteristics of these materials and understand how plant resistance can help manage this insect. This study was carried out in a laboratory at 26±2 ºC and 60±10% R.H (relative humidity). Fifty insects were kept in each hybrid, each insect was considered one repetition. According to biological parameters and fertility life table, hybrids BRS373, DKB590 and 50A10 were less suitable for the sugarcane aphid multiplication. Thus, these hybrids could be useful to manage this pest, since the population growth speed is one of the worst problems for the implementation of cropping systems. Genotypes AG1090, MSK327 and XGN1305 favored the development of this pest and, when chosen within a cropping system, other management strategies should be considered.